Practical programming in Tcl and Tk - Welch, Brent B. (Prentice Hall, 1995)
Tcl fundamentals; Strings and pattern matching; Tcl data structures; Control flow commands; Procedures and scope; Eval; Working with UNIX; Reflection and debugging; Script libraries; Tk fundamentals; Tk by example; The pack geometry manager; Binding commands to X events..